2019
DOI: 10.1111/jphd.12335
|View full text |Cite
|
Sign up to set email alerts
|

Methodological approaches for investigating links between dental and chronic diseases with claims data: A scoping study

Abstract: Objectives: The purpose of this study was to provide an overview of methodological approaches to assess the relationship between dental diseases and other noncommunicable diseases on the basis of claims data. Methods: Based on the methodological framework of Arksey and O'Malley, a scoping study was conducted. By searching electronic databases (PubMed, Web of Science, and LILACS), appropriate articles were identified. After extracting relevant information and entering it into a data-charting form, the study cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
(182 reference statements)
0
1
0
Order By: Relevance
“…Recent study have reported that PISA is effectively associated with systemic markers of low-grade inflammation, such as C-reactive protein [12]. Periodontal disease is a risk factor for non-communicable diseases through the localized inflammation and periodontal pathogens [13][14][15][16][17][18][19][20]. Therefore, PISA may be an optimal index to investigate the correlation between periodontal disease and non-communicable diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study have reported that PISA is effectively associated with systemic markers of low-grade inflammation, such as C-reactive protein [12]. Periodontal disease is a risk factor for non-communicable diseases through the localized inflammation and periodontal pathogens [13][14][15][16][17][18][19][20]. Therefore, PISA may be an optimal index to investigate the correlation between periodontal disease and non-communicable diseases.…”
Section: Introductionmentioning
confidence: 99%